Blended Learning Design to Support Differentiated Learning: A Case Study for Students with Disability - Utami, Iga Setia; Budi, Setia; Arnez, Gaby; Hafid, Afdhil (Department of Special Education, 2024)
Blended learning has been gaining attention in recent years as a method of instruction that combines online and offline learning experiences. This approach can potentially support differentiated learning for students with disabilities, who often require individualized instruction and accommodations. The purpose of this paper is to describe how the blended learning models can be used to support differentiated learning needed by students with special needs in higher education. This study is a qualitative case study. Data was obtained through observation, literature study, documentation and interviews with students and experts on the appropriate learning models for students with disabilities to be implemented in higher education. The findings of this research are in the form of a learning model design with a combination of face-to-face and online lectures through appropriate technology to support differentiated learning for each student with disabilities.